Competitiveness Analysis of Indonesian Frozen Shrimp Exports to China Using RCA and EPD - Ardian Christyanti; Taufik Setyadi; Dona Wahyuning Laily (Grouper, 2026)
Indonesia is one of the world's major exporters of frozen shrimp, but its market share in China is still relatively small despite the country's high demand. This study aims to analyze the trend of Indonesia's frozen shrimp export performance to China, analyze comparative competitiveness using Revealed Comparative Advantage (RCA) analysis, analyze competitiveness dynamics through Export Product Dynamic (EPD), and formulate strategies to improve export competitiveness. The study used secondary time series data (2014-2023) obtained from BPS, KKP, UN Comtrade, and other official sources. The results showed that the trend of Indonesia's frozen shrimp exports to China fluctuates but tends to increase, with a significant spike in 2022. The RCA analysis shows that Indonesia's comparative competitiveness was strong at the beginning of the period, but weakened since 2019-2023 as the RCA value is consistently below one. Meanwhile, the EPD analysis shows that Indonesia's export position is often in the Lost Opportunities category, signaling a failure to capitalize on market growth despite growing Chinese demand. These findings indicate the need for strategies to strengthen competitiveness through market diversification, modernization of cultivation systems, improved logistics efficiency, implementation of international standards, and more aggressive promotion and branding in the Chinese market.